8B.03: ATHEROMA PROGRESSION IN RENAL ARTERIES AFTER CATHETER-BASED RENAL ARTERY DENERVATION USING SERIAL VOLUMETRIC COMPUTED TOMOGRAPHY ANALYSIS. (June 2015) - Worthley, S.; Kataoka, Y.; Nicholls, S.; Sidharta, S.; Worthley, M.; Tsioufis, C.; Papademetriou, V.
Abstract : Objective: We analysed the renal artery wall using serial high resolution CT image analysis before and at 6 months after renal artery denervation in the EnligHTN 1 trial. Design and method: The EnligHTN-I study was a prospective, multi-center, non-randomized study to evaluate the clinical efficacy of the EnligHTN TM multi-electrode radiofrequency ablation catheter in resistant hypertensive patients. 40 patients with serial renal artery CT imaging were analyzed. Cross-sectional images of renal arteries at 1-mm interval were acquired by a commercially available software (3-mensio, Structural heart, ver 5.1). The luminal and outer wall boundaries of renal arteries were manually traced at 1 mm interval. Total atheroma volume (TAV) was calculated by summation of the plaque area which was the difference between the lumen and vessel wall areas. Percent atheroma volume (PAV) was calculated as the proportion of vessel wall volume occupied by plaque volume. Results: On serial evaluation, greater progression of PAV and TAV was observed in the proximal zone (Change in PAV, 6.9 ± 0.6 vs. 4.4 ± 0.6; p = 0.01, change in TAV, 76.9 ± 12.9 vs. 17.9 ± 12.9, p = 0.002). Receiver-operating characteristics analysis demonstrated that baseline PAV in the ablation zone > 38.1% was an optimal cut-off value to predict its substantial progression at 6 months after the procedure (AUC = 0.83, sensitivity 90.0%, specificity 74.3%). Interestingly, the change in PAV and lumen areas were associated with reduction in office BP in the distal segment (p = 0.0142 and 0.0226 respectively), but not in the poroximal segment. This could suggest that ablations occurring in the more distal segment may be more effective at inducing renal denervation and therefore inducing a BP reduction, than the more proximal segment. Conclusions: Renal artery denervation with the EnligHTN multi-electrode catheter was associated with subsequent vessel wall thickening of the renal arteries. Proximal position and larger atheroma volume at baseline were predictors for a greater increase in vessel wall thickness. By performing ablations more distally and avoiding those with more significant atherosclerotic disease may well reduce the risk of renal artery stenosis after renal artery denervation and potentially lead to a more efficacious renal denervation procedure.